Two Mode - (De)muxer Based on a Symmetric Y Junction Coupler, a \(2× 2\) MMI Coupler and a Ridge Phase Shifter Using Silicon Waveguides for WDM Applications - Truong, Dung Cao; Vu, Dao Anh; Hoang, Chung Vu (Communications in Physics, 2017)
In this paper, we introduce a new two-mode (de)multiplexer based on the silicon-on-insulator (SOI) platform. The device is built on a symmetric Y-junction, a 2×2 multimode interference (MMI) waveguide and a phaseshifter in the form of a ridge waveguide which is designed using 3D scalar beam propagation method (BPM). The phase evolution in the structure is discussed in details. Simulation results show that the device can operate in a wide wavelength range (150 nm) with a low insertion loss and small crosstalk. Large fabrication tolerance to the width of the input waveguide up to 100 nm is achieved, which is compatible to the current CMOS manufacturing technologies for the photonic integrated circuits. Furthermore, the small footprint (4µm×286µm) makes the device suitable for applications in high bitrate and compact on-chip silicon photonic integrated circuits.